Updated overall survival data and predictive biomarkers of autologous NK cells plus Sintilimab as second-line treatment for advanced non-small cell lung cancer - Jia, Lin; Chen, Naifei; Chen, Xiao; Niu, Chao; Liu, Ziling; Ma, Kewei; Yang, Lei; Zhao, Yuguang; Song, Wei; Lu, Jin; Chen, Chen; Cong, Xiaofeng; et al. (Frontiers in Immunology, 2025)
PurposeCombination strategies involving immune checkpoint inhibitors (ICIs) have been a prominent focus of research in the treatment of non-small cell lung cancer (NSCLC). Our prior findings demonstrated that the combination of autologous NK cells with the PD-1 antibody (Sintilimab), offered promising efficacy in NSCLC patients who failed the first-line platinum-based chemotherapy. Here, we present updated overall survival (OS) data from the final analysis, aiming to identify patient subgroups that derive maximal benefit from this therapeutic approach.MethodsTwenty NSCLC patients without driver gene mutations were enrolled and treated with a combination of autologous NK cells and Sintilimab every three weeks. Multicolor immunofluorescence staining was applied to evaluate static markers within the tumor microenvironment. Concurrently, dynamic assessments were conducted using next-generation sequencing and monitoring of PD-1/PD-L1 expression on NK cells to identify patient populations with favorable prognoses.ResultsThe median OS was 27.3 months (95% CI, 0.76 to 53.8), with six patients still alive at the follow-up cutoff. A significant correlation was observed between the CD56+PD-L1+ cellular phenotype and extended survival. Clearance of circulating tumor DNA (ctDNA) and an increased percentage of PD-L1+ NK cells following treatment was associated with significantly better survival outcomes. Notably, prolonged treatment exposure did not lead to increased toxicity.ConclusionThe combination of autologous NK cells with Sintilimab significantly enhances long-term survival in NSCLC patients without exacerbating adverse effects, presenting a promising strategy for future combination immunotherapy approaches in NSCLC treatment.Clinical trial registrationhttps://www.clinicaltrials.gov/ct2/show/NCT03958097, identifier NCT03958097.